2007
DOI: 10.1002/ajhb.20701
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of estimation of age at menarche by various methods in women participating in the Krakow Longitudinal Growth Study, Poland

Abstract: The purpose of this study was to see whether menarcheal age assessment by means of the most frequently used methods that were conducted every time on the same group of girls would yield the same results. One hundred and one Polish girls, whose ages at menarche were recorded in a longitudinal study between 1976 and 1990, were asked to recall the age of menarche in 2004. The mean menarcheal ages of those women were calculated by means of the probit (PA), prospective (AA), retrospective method without age correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Furthermore, some studies report that recall diminishes with age, while others report no age effect [87]. Recall of menarcheal age may also be faulty for women, although one study showed that it was equally likely to be overestimated by 1 year as underestimated by 1 year [88].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies report that recall diminishes with age, while others report no age effect [87]. Recall of menarcheal age may also be faulty for women, although one study showed that it was equally likely to be overestimated by 1 year as underestimated by 1 year [88].…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the average age of the onset of menstruation, probity models were fitted to the proportion of girls at each age who had reached menarche. This approach, sometimes referred to as the status quo method, is mainly used in cross sectional studies of children and adolescents [21–23]. The status quo method is employed to estimate the mean age at menarche by studying all data concerning girls from the analysed group, whereas the retrospective method can only be used for girls who have already reached menarche [21].…”
Section: Methodsmentioning
confidence: 99%
“…This approach, sometimes referred to as the status quo method, is mainly used in cross sectional studies of children and adolescents [21–23]. The status quo method is employed to estimate the mean age at menarche by studying all data concerning girls from the analysed group, whereas the retrospective method can only be used for girls who have already reached menarche [21]. The calculation was carried out as follows: ages were recorded and calculated as decimals (e.g., 8.00–8.99 years, 9.00–9.99 years).…”
Section: Methodsmentioning
confidence: 99%
“…The available literature also prevented us from analyzing studies separately according to different methods of measuring mean AAM. While we included studies based both on probit methods and on retrospective recollection, previous studies reported contradictory results depending on the methodology [63,64]. Data for AAM in different ethnic groups was only available for early studies [49,61] and was, therefore, not included in the current analysis.…”
Section: Discussionmentioning
confidence: 99%